2022
DOI: 10.21203/rs.3.rs-1435993/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common anti-cancer therapies induce somatic mutations in stem cells of healthy tissue

Abstract: Comprehensive analyses of genome-wide mutation profiles has revealed that specific anti-cancer drugs, such as 5-fluorouracil (5-FU), are highly mutagenic to cancer cells and cultured cells. The systemic administration of these chemotherapies presents a potential genotoxic hazard to healthy tissues, however, the true mutational impact on normal cells of patients is not known. Here, we examined genome-wide somatic mutation patterns in healthy adult stem cells (ASCs) of the colon or the liver from 14 colorectal c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…1e), these features were generally more prevalent in patients with metastatic tumors and thus very likely contributed to the observed SV increase in metastatic tumors. Finally, prior exposure to radiotherapy treatment was strongly associated with small deletions in breast and prostate cancers (in agreement with radiotherapy-treated secondary malignancies 55 , gliomas 37 , and healthy tissue 56 ). This suggests that, among common anti-cancer therapies, radiotherapy in particular significantly contributes to the SV landscape in treatment-surviving cancer cells.…”
Section: Genomic and Clinical Features Associated With Structural Var...supporting
confidence: 69%
“…1e), these features were generally more prevalent in patients with metastatic tumors and thus very likely contributed to the observed SV increase in metastatic tumors. Finally, prior exposure to radiotherapy treatment was strongly associated with small deletions in breast and prostate cancers (in agreement with radiotherapy-treated secondary malignancies 55 , gliomas 37 , and healthy tissue 56 ). This suggests that, among common anti-cancer therapies, radiotherapy in particular significantly contributes to the SV landscape in treatment-surviving cancer cells.…”
Section: Genomic and Clinical Features Associated With Structural Var...supporting
confidence: 69%
“…Finally, prior exposure to radiotherapy treatment was strongly associated with small deletions in breast and prostate cancers (in agreement with radiotherapy-treated secondary malignancies [109], gliomas [172], and healthy tissue [271]). This suggests that, among common anti-cancer therapies, radiotherapy in particular significantly contributes to the SV landscape in treatment-surviving cancer cells.…”
Section: Genomic and Clinical Features Associated With Structural Var...supporting
confidence: 67%
“…Though 5-Fluorouracil is known to leave a distinct SBS signature (SBS17a), no evidence of it was seen in this cohort, in line with its mechanism of mutagenicity on dividing – and not quiescent – cells 12 . Conversely, adducts generated by melphalan-and platinum-based agents are not dependent on cell turnover 9, 12 and induce mutagenesis in tumor and normal tissues 19, 20 . In fact, the mutational burden between de novo AML and tMN without melphalan or platinum exposure were strikingly similar (Wilcoxon test, p = 0.587; Fig 1e ), adding evidence that chemotherapies typically associated with tMN may facilitate malignancy in absence of any appreciable increase in SBS mutagenesis 12 .…”
Section: The Mutational Landscape Of Therapy-related Malignanciesmentioning
confidence: 99%
“…It has been suggested that anti-cancer therapies exert positive selective pressure on CH bearing pre-leukemic driver mutations and that expansion is not contingent on the increased mutational burden relative to de novo AML 17, 18 with speculation that other cellular machinery may be altered by exposure. Despite this, distinct DNA-damaging cytotoxic agents can measurably alter the mutational profile in each exposed cell, including in normal tissue 6, 19, 20 . The application of mutational signatures to whole genome sequencing (WGS) data has allowed for direct quantitation of chemotherapy-mediated DNA damage and revealed that a subset of tMN with prior platinum exposure do indeed have an increased, chemotherapy-specific, mutational burden as compared to non-platinum-exposed tMN 12 .…”
mentioning
confidence: 99%